EFEKTIVITAS SISTEM KEMITRAAN UPTD BENIH DAN PERLINDUNGAN TANAMAN PANGAN, HORTIKULTURA DAN PERKEBUNAN DENGAN PETANI PENANGKAR UNTUK MEMENUHI KEBUTUHAN BENIH PADI - herni is sumayanti; Aliudin Aliudin; Nurmayulis Nurmayulis (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2020)
The research aims to analyze and evaluate the system of partnership between UPTD BPTPHP Banten Province with rice seed grower farmers and measure the level of satisfaction of rice seed grower farmers in partnership with UPTD BPTPHP Banten Province on the course of the pertnership. Qualitative analysis is done through data collection methods in the form of interviews and questionnaires conducted on selected respondents with a purpossive sampling method. The result showed that the partnership system established between UPTD BPTPHP and rice seed breeding farmers in Banten Provnce was a plasma core partnership. The level of importance and satisfaction of farmers is measured using a Likert scale with four categories and is calculated using the Importance Performance Analysis (IPA). Conformity analysis is done by comparing the total score of performance level with the total score of importance level. The value of partner farmer’s satisfaction with partnership performance is stated in letter X, while the level of importance (expectations) of farmers is stated in letter Y. The level of satisfaction of partner farmers is measured by the Customer Satisfaction Index (CSI) method that determines the level of overall satisfaction of partner farmers based on quality attributes measured services. Based on the analysis of Importance Performance Analysis (IPA) it is known that the average value for the level of importance is 3,42. Attributes with importance are above the average of 8 attributes that are above the average of 8 attributes. The level of satisfaction obtained an average value of 2,97 with the number of attributes that are above the average of 8 attributes. In general it is known that the farmers feel satisfied, because the CSI value obtained is 68,44.